2020
DOI: 10.31183/imcp.2020.00048
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-potentiation activities of three animal species extracts, Bitis arietans, Helix aspersa, and Aristaeomorpha foliacea and mode of action against MDR Gram-negative bacteria phenotypes

Abstract: Background: In recent years, drug resistance to human pathogenic bacteria has been commonly reported from all over the world. As antimicrobial activities of most medicinal plants and antibiotics have been already explored, it is more important to make investigations on animal species mainly invertebrates which could constitute an efficient source of antimicrobial molecules. This work was aimed at contributing to the fight against microbial resistance through the study of antibacterial potential of three animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The combination assay was performed as previously described, with some modifications made during the procedure [ 4 , 7 ]. The test was briefly performed by introducing 100 μL of MHB into the wells of a 96-well microplate, followed by the addition of 100 μL of the test antibiotics in the first well of each column and progressive dilution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination assay was performed as previously described, with some modifications made during the procedure [ 4 , 7 ]. The test was briefly performed by introducing 100 μL of MHB into the wells of a 96-well microplate, followed by the addition of 100 μL of the test antibiotics in the first well of each column and progressive dilution.…”
Section: Methodsmentioning
confidence: 99%
“…The WHO has stated that most of the developing world still benefits from the use of traditional medicines derived from medicinal plants [3]. Moreover, many studies revealed the antibacterial inhibition activity of botanicals from African medicinal plants against MDR bacteria [4][5][6][7][8][9]. Several constituents including triterpenoids, phenolics, as well as alkaloids isolated from African medicinal plants were also documented for their antibacterial activities [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The ethanolic extract's ability to inhibit H+-ATPase proton pumps in S. aureus ATCC 6835 was evaluated by monitoring medium acidification, following Guefack Fofack et al [23] with modifications. Bacterial cultures underwent glucose starvation, pH adjustment, and incubation with extract at MIC and 2x MIC.…”
Section: Evaluation Of the Extract's Effect On Bacterial H+-atpase Pr...mentioning
confidence: 99%
“…The MIC and MBC of the tested bacteria were determined by the broth microdilution INT colorimetric assay as previously described [37,38]. The tested samples (plant extract, fractions, some of the isolated compounds, and chloramphenicol) were dissolved in DMSO/MHB.…”
Section: Antimicrobial Activitymentioning
confidence: 99%